GRAMMAR TOPIC EXPLORATION AND APPLICATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the development of a group of secondary school students learning English grammar, focusing on interrogative sentence structures. The paper highlights learner profiles, instructional approaches, and selected grammar topics. It also explores how meaning-focused input and output, deductive techniques, and communicative activities can support effective grammar instruction at the A2–B1 level.